China's “dynamic clearing” epidemic prevention policy: Achievements, challenges, and prospects - Wang, Quansheng; Huang, Lansong (Frontiers in Public Health, 2022)
The COVID-19 outbreak makes up a major public health emergency, and each country has adopted different epidemic prevention policies and measures. Since the control of COVID-19 in 2020, China has gradually developed a “Dynamic Clearing” epidemic prevention policy of “external input prevention and internal rebound prevention”. The policy has been effective in protecting people's lives and health and developing the country's economy as much as possible, but it has also faced some challenges, such as slowing economic development, huge prevention, and control costs, and expanding secondary disasters and risks. Reviewing China's current “dynamic clearing” policy, it is still the overall policy to continuously improve guiding policies, construct scientific prevention measures, and promote digital governance at the grassroots level.